1979
DOI: 10.1111/j.1749-6632.1979.tb47139.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Regression Induced in Mice by Partially Purified Lymphokine Fractions*

Abstract: Over the past six years our studies have involved the use of cell-free supernatants derived from long term cultures of human and mouse lymphoblast cellThe properties of lymphocyte mediators (lymphokines) have been extensively reviewed 4 9 and a recent workshop summary on this subject covers basic and clinical aspects.'j Human peripheral blood lymphocytes have proved to be rich sources of lymphokine-containing supernatants and have been used for most studies on in vitro lymphokine properties. We have used lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A similar PBA can be generated in high density rabbit lymphocyte cultures ( 5 ) or in the serum of rabbits inoculated intravenously with allogeneic lymphoid cells (6). Also, lymphokine activity has been found to be associated with a2M in supernatants of the normal human lymphoblastoid cell line RPMI 1788 (7). Recently, it has been shown that intraarticular injection of a2M-protease complexes into rabbits results in histopathologic changes that suggest similarities to those observed in RA patients (8).…”
mentioning
confidence: 95%
“…A similar PBA can be generated in high density rabbit lymphocyte cultures ( 5 ) or in the serum of rabbits inoculated intravenously with allogeneic lymphoid cells (6). Also, lymphokine activity has been found to be associated with a2M in supernatants of the normal human lymphoblastoid cell line RPMI 1788 (7). Recently, it has been shown that intraarticular injection of a2M-protease complexes into rabbits results in histopathologic changes that suggest similarities to those observed in RA patients (8).…”
mentioning
confidence: 95%
“…The properties and functions of lymphokines, including those exhibiting cytotoxic activity, have been recently reviewed (Cohen et al, 1979). Lymphotoxin, a lymphokine produced by mitogen or antigenstimulated-lymphocytes, inhibits tumor cell growth in vivo May-Levin et al, 1972;Papermaster et al, 1974Papermaster et al, , 1976Papermaster et al, , 1979 and in vitro (Gately et al, 1976;Rosenberg et al, 1973;Sawada et al, 1976;Williams and Granger, 1973). Furthermore, lymphotoxin is frequently many times more effective in vitro as a growth inhibitor of a variety of tumor cells than of non-tumorigenic cells from the same species (Evans et al, 1975;Meltzer and Bartlett, 1972;Rundell and Evans, 1981;Weedon et al, 1973).…”
mentioning
confidence: 99%